Desain Fasilitas Umum Sebagai Tempat Bersosialisasi pada Royal Apartment - Yunian Lie; Tri Noviyanto Utomo; Maria Yohana Susan (Universitas Ciputra Surabaya, 2015)
Within the development of property in Indonesia, Makassar is one of the city with the fastest development in property. This development in property make a great support for the economical growth in Makassar for the recent years. The development property in Makassar increase significantly, one of the development that could be seen are the multi storey building like Apartment and hotel combined with shopping centre and restaurant. Also, this development are supported by the lifestyle change from the citizen that tend to follow the lifestyle of the citizen in the other big cities such as Jakarta and Surabaya. Royal Apartment is the first apartment in Makassar that is located in Topaz Raya, Panakukang Block where Panakukang Mas Block is one of the commercial area because Panakukang Mas is one of the elite area in Makassar and have easy access to the shopping centre and housing. Royal Apartment is the first apartment in Makassar with so much facility to offer like restaurant and fitness centre. For designing the public facilities of Royal Apartment, the concept offered are dynamic and fun. In line with the design’s characteristi, geometeric shapes is applied as to create a dynamic design of public facilities, while graphics is applied as to give the impression of fun design.